Being the Victim of Intimate Partner Violence in Virtual Reality: First- Versus Third-Person Perspective - Gonzalez-Liencres, Cristina; Zapata, Luis E.; Iruretagoyena, Guillermo; Seinfeld, Sofia; Perez-Mendez, Lorena; Arroyo-Palacios, Jorge; Borland, David; Slater, Mel; Sanchez-Vives, Maria V. (Frontiers in Psychology, 2020)
Immersive virtual reality is widely used for research and clinical purposes. Here we explored the impact of an immersive virtual scene of intimate partner violence experienced from the victim’s perspective (first person), as opposed to witnessing it as an observer (third person). We are ultimately interested on the potential of this approach to rehabilitate batterers and in understanding mechanisms underlying this process. For this, non-offender men experienced the scene either from the perspective of the victim’s virtual body (a female avatar), which moved synchronously with the participants’ real movements, or from the perspective of an observer, while we recorded their behavior and physiological responses. We also evaluated through questionnaires, interviews and implicit association tests their subjective impressions and potential pre/post changes in implicit gender bias following the experience. We found that in all participants, regardless of perspective, the magnitude of the physiological reactions to virtual threatening stimuli was related to how vulnerable they felt for being a woman, the sensation that they could be assaulted, how useful the scene could be for batterer rehabilitation, and how different it would have been to experience the scenario on TV. Further, we found that their level of identification with the female avatar correlated with the decrease in prejudice against women. Although the first-person perspective (1PP) facilitated taking the scene personally, generated a sensation of fear, helplessness, and vulnerability, and tended to induce greater behavioral and physiological reactions, we show that the potential for batterer rehabilitation originates from presence and identification with the victim, which in turn is more easily, but not exclusively, achieved through 1PP. This study is relevant for the development of advanced virtual reality tools for clinical purposes.